2010
DOI: 10.1371/journal.pone.0010154
|View full text |Cite
|
Sign up to set email alerts
|

The Cost-Effectiveness of Directly Observed Highly-Active Antiretroviral Therapy in the Third Trimester in HIV-Infected Pregnant Women

Abstract: BackgroundIn HIV-infected pregnant women, viral suppression prevents mother-to-child HIV transmission. Directly observed highly-active antiretroviral therapy (HAART) enhances virological suppression, and could prevent transmission. Our objective was to project the effectiveness and cost-effectiveness of directly observed administration of antiretroviral drugs in pregnancy.Methods and FindingsA mathematical model was created to simulate cohorts of one million asymptomatic HIV-infected pregnant women on HAART, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
54
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(55 citation statements)
references
References 76 publications
0
54
0
1
Order By: Relevance
“…The recent changes in WHO recommendations to consider where feasible, the use of cART (instead of single-dose NVP) for prophylaxis in pregnant women reflect the increased effectiveness in PMTCT of longer and more complex regimens [2, 8587] for the mother coupled with extension of maternal or infant prophylaxis during the neonatal/breastfeeding period [8890]. The WHO has also endorsed consideration of the approach of initiating life-long cART in all pregnant women regardless of CD4 count, which has been adopted as national policy in Malawi [91, 92]. These new recommendations reflect the benefits of earlier initiation of ART for maternal health and infant survival, as well as to optimize PMTCT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent changes in WHO recommendations to consider where feasible, the use of cART (instead of single-dose NVP) for prophylaxis in pregnant women reflect the increased effectiveness in PMTCT of longer and more complex regimens [2, 8587] for the mother coupled with extension of maternal or infant prophylaxis during the neonatal/breastfeeding period [8890]. The WHO has also endorsed consideration of the approach of initiating life-long cART in all pregnant women regardless of CD4 count, which has been adopted as national policy in Malawi [91, 92]. These new recommendations reflect the benefits of earlier initiation of ART for maternal health and infant survival, as well as to optimize PMTCT.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a trial with peer mentors to improve maternal ART adherence antenatally and at the time of birth is underway in South Africa [90]. Furthermore, using a mathematical model McCabe et al [91] found that programs aimed at optimizing ART adherence using directly observed therapy would be cost-effective to decrease MTCT. Another trial, also underway in South Africa, is investing the role of male involvement on PMTCT ART adherence [92].…”
Section: Discussionmentioning
confidence: 99%
“…The models examined how a variety of HIV interventions such as vaccination [17-22], circumcision [23,24], condom usage [25-32], reduction in concurrency [25,26,29,32-34], HIV testing [15,28,35-37], anti-retroviral treatment [19,22,37-39], STD control [25,29,30,40-45], and prevention of mother to child transmission [18,46,47] can affect HIV incidence and prevalence in a wide variety of settings including North America [15,26,46], Australia [20,35,36] and sub-Saharan Africa [18,19,21,23-25,27,29,30,32-34,37-45,47]. These analyses were able to discuss the effects of interventions in less researched and accessible populations like MSM [15,17,20,22,26,28,35,36] and IDU [15,48].…”
Section: Discussionmentioning
confidence: 99%
“…17,20 Our group and others have used creative approaches to optimising adherence, including the use of directly observed therapy on labour and delivery units. [27][28][29][30][31] We also found that use of an NNRTI-based regimen may be associated with increased likelihood of achieving a viral load < 400 copies/ml and <1000 copies/ml. Given updated Centers for Disease Control and Prevention guidelines recommending third-trimester HIV antibody screening in many settings across the USA, there may be an increasing proportion of HIV-infected pregnant women identified later in pregnancy.…”
Section: Discussionmentioning
confidence: 77%